Genome-wide association mapping for field spot blotch resistance in South Asian spring wheat genotypes - Kamble, Umesh; Xinyao He; Sudhir Navathe; Kumar, Manjeet; Patial, Madhu; Kabir, Muhammad Rezaul; Singh, Gyanendra; Singh, Gyanendra Pratap; Joshi, Arun Kumar; Pawan Kumar Singh (Wiley, 2024)
Spot blotch caused by Bipolaris sorokiniana ((Sacc.) Shoemaker) (teleomorph: Cochliobolus sativus [Ito and Kuribayashi] Drechsler ex Dastur) is an economically important disease of warm and humid regions. The present study focused on identifying resistant genotypes and single-nucleotide polymorphism (SNP) markers associated with spot blotch resistance in a panel of 174 bread spring wheat lines using field screening and genome-wide association mapping strategies. Field experiments were conducted in Agua Fria, Mexico, during the 2019–2020 and 2020–2021 cropping seasons. A wide range of phenotypic variation was observed among genotypes tested during both years. Twenty SNP markers showed significant association with spot blotch resistance on 15 chromosomes, namely, 1A, 1B, 2A, 2B, 2D, 3A, 3B, 4B, 4D, 5A, 5B, 6A, 6B, 7A, and 7B. Of these, two consistently significant SNPs on 5A, TA003225-0566 and TA003225-1427, may represent a new resistance quantitative trait loci. Further, in the proximity of Tsn1 on 5B, AX-94435238 was the most stable and consistent in both years. The identified genomic regions could be deployed to develop spot blotch-resistant genotypes, particularly in the spot blotch-vulnerable wheat growing areas.